The 1,500-m rowing performance is highly dependent on modified wingate anaerobic test performance in national-level adolescent rowers - Maciejewski, H.; Rahmani, A.; Chorin, F.; Lardy, J.; Giroux, C.; Ratel, S. (Pediatric Exercise Science, 2016)
Purpose: The aim of the current study was to determine whether the anaerobic performance assessed by a modified Wingate test could account for the 1,500-m rowing ergometer performance in young competitive rowers. Methods: Fourteen national-level adolescent rowers performed on a rowing ergometer i) a 30-s allout exercise (i.e., modified Wingate test) and ii) a 1,500-m all-out exercise (i.e., rowing performance). For each of these two exercises, the mean power output was considered as the main performance criterion (PWIN and P1500, respectively). Results: PWIN was correlated to P1500 (r2 = .83, p < .0001, ß = 100%). Furthermore, the estimated total muscle mass was correlated to PWIN and P1500 (r2 = .72 and r2 = .83, p < .0001, ß = 100%, respectively). The allometric scaling also indicated that total muscle mass accounts 62% for the relationship between PWIN and P1500. Conclusion: Our results highlight the importance of considering the contribution of total muscle mass and anaerobic energy pathways to 1,500-m rowing performance in competitive adolescent rowers. Therefore, the modified Wingate test could be used by rowing coaches to potentially identify talented young rowers.